Can paediatric medical students devise a satisfactory standard of examination for their colleagues?. Issue 6 (1st June 1999) - Cunningham, Steven
Abstract : OBJECTIVES: To determine what standard paediatric medical students would set for examining their peers and how that would compare with the university standard. DESIGN: Single blinded computer marked examination with questionnaire. SETTING: University medical school. SUBJECTS: Medical students during their final paediatric attachment. INTERVENTIONS: Medical students asked to derive 10, five branch negatively marked multiple choice questions (MCQs) to a standard that would fail those without sufficient knowledge. Each 10 were then assessed by another student as to the degree of difficulty and the relevance to paediatrics. One year later student peers sat a mock MCQ examination derived from a random 40 questions (unaware that the mock MCQs had been derived by peers). MAIN OUTCOME MEASURES: Comparison of marks obtained in mock and final MCQ examinations; student perception of the standard in the two examinations assessed by questionnaire. RESULTS: 44 students derived 439 questions, of which 83% were considered an appropriate standard by a classmate. One year later 62 students sat the mock examination. Distribution of marks was better in the mock MCQ examination than the final MCQ examination. Students considered the mock questions to be a more appropriate standard (72% v 31%) and the topics more relevant (88% v 64%) to paediatric medical students. Questions were of a similar clarity in both examinations (73% v 78%). CONCLUSIONS: Students in this study were able to derive an examination of a satisfactory standard for their peers. Involvement of students in deriving examination standards may give them a better appreciation of how standards should be set and maintained.